Hydrolyzed glucomannan-maltodextrin matrices for high-efficiency spray-dried iron encapsulation - Wardhani, Dyah Hesti; Cahyono, Heri; Ulya, Hana Nikma; Fauzia, Rizka Savira Noor; Dewanti, Salma Rahma; Sumarsih, Eni; Kumoro, Andri Cahyo; Anam, Khairul; Vazquez, José Antonio (Penerbit Universiti Kebangsaan Malaysia, 2026)
Efficient encapsulation of iron is crucial to enhance its stability, maintain functionality, and ensure cost-effective application in food systems. In this study, a novel encapsulation matrix combining hydrolyzed glucomannan and maltodextrin was developed to produce spray-dried iron particles with improved physicochemical properties. The effects of drying temperature (60-90 °C), glucomannan concentration (1-3%), and iron content (20-30 mg/g matrix) were systematically evaluated. Increasing these parameters significantly enhanced water-particle interactions, resulting in higher solubility, swelling capacity, and wettability. The best-performing formulation - 30 mg iron/g matrix, 3% hydrolyzed glucomannan, and 30% maltodextrin - achieved an encapsulation efficiency of 98.4%. Morphological and structural analyses showed that the particles contained uniformly distributed iron, had reduced particle size, and exhibited superior thermal stability. These characteristics not only contribute to improved storage stability but also facilitate rapid dispersion in aqueous systems, enhancing bioavailability potential. Overall, this work demonstrates the effectiveness of hydrolyzed glucomannan maltodextrin blends as encapsulation matrices for producing stable, functional iron powders. The approach offers a promising, energy-efficient strategy for food fortification, with potential applications in addressing iron deficiency through more effective and consumer-friendly delivery systems.